Information Technology and E-Governance : Comparative Policy Perspective of India and Assam - Mili, Monika (International Journal of Advanced Science and Technology, 2019)
E-Governance or electronic governance relates to the integration of Information and Communication Technology (ICT) within all governmental processes. The main purpose of e-Governance is to enhance the Government’s ability to address the needs of its people in a convenient, efficient and transparent manner.In this era of information technology, digital revolution and evolution from mouse clicks to touch pads, on-premise solutions to replication of a real life scenario through digital twins, is fast becoming the determining factor for providing farfetched solutions to socio-economic problems. Information Communication Technology has not only taken up the rudder of providing solutions but also, has become the compass for identifying and determining bottlenecks. The government has already realised the importance of ICT and in this regard embarked many initiatives to digitally empower the status of common man by bringing e-Governance in almost all the departments. By amalgamating management and sectoral expertise coupled with cutting edge technology expertise, the IT & e-Governance practice continues to fulfil, the motto of efficient service delivery for various Government and Non-Government domains enriching the lives of billions of people across globe.In India, the ICT initiatives have been implemented focussing on the development of rural economies with a promise of enhanced public participation in the governance. Though such initiatives, to a reasonable extent, have been able to increase people’s participation in the governance process, it is not free from its own impediments. In this context, the study attempts to explore the challenges of ICT and e- governance in Assam.